Pharmacokinetics, biodistribution and neuroprotective effects of thymoquinone-loaded nanostructured lipid carrier on high fat cholesterol diet induced Alzheimer's disease rat model - Zakarial Ansar, Fatin Hannani (2022)
Alzheimer's disease (AD) is one of the ultimate forms of dementia in people 65 years of age and older, slowly growing out of slight forgetfulness to the requirement for comprehensive care. Globally, close to 36 million people suffer from Alzheimer's disease or related dementia. In Malaysia, there are approximately 50,000 people with AD. One of the traditional AD risks is hypercholesterolemia. Hypercholesterolemia is commonly linked to oxidative stress and lipid oxidation which play an important role in the development of AD. Currently, there is still no viable cure for AD. Thus, the need for therapies that offer neuroprotective properties is in demand. One of the promising approaches is the use of the natural product. Thymoquinone (TQ), a bioactive compound from Nigella sativa that exhibit antioxidant property, can protect the neuron cells from degrading. Nevertheless, TQ has low solubility in blood and poor oral bioavailability. Consequently, a nanostructured lipid carrier (NLC) has been developed as a drug delivery vehicle to overcome the limitations of TQ (herein referred to as TQ-NLC). This study aimed to determine the role of oral and intravenous administration in pharmacokinetics and bioavailability of TQ-NLC as well as the neuroprotective effects of TQ-NLC as a potential drug candidate for the management of AD. The pharmacokinetics and biodistribution study of TQNLC was carried out in healthy male Sprague Dawley rats via oral and intravenous administration (100 and 25 mg/kg, respectively) using gamma ray counter and gamma camera. In vivo study of neuroprotective effect of TQ-NLC via oral administration (12.5, 25 and 50 mg/kg) includes Morris water maze test, lipid profile level, neurodegenerative features, oxidative stress level and protein expression analysis. Oral administration of TQ-NLC demonstrated improved relative bioavailability compared with intravenous administration. The movement of TQ-NLC through the intestinal lymphatic system is postulated to bypass the first metabolism, thus, increasing the relative bioavailability. However, oral administration is more slowly absorbed as the AUC0-∞ was 4.539 times lower than intravenous administration. During the Morris water maze test, the animals treated with 25 mg/kg of TQ-NLC showed an increase in the time spent at the targeted quadrant and reduced total cholesterol compared to the negative control (untreated) (p<0.05). In addition, the animals treated with 25 mg/kg of TQ-NLC showed shorter escape latency in comparison to the negative control (untreated), but it was not statistically significant. In addition, the animals treated with 50 mg/kg of TQ-NLC showed a reduction in MDA level and protein carbonyl compared to negative control (untreated). Protein analyses in the brain hippocampus revealed reduction in levels of the Aβ, BACE1 and ApoE while enhanced the Aβ clearance and degradation by increasing the level of IDE and LRP1 in the brain. In conclusion, in vivo data demonstrated the beneficial effects of TQ-NLC in ameliorating neurodegenerative changes particularly in AD biomarkers through the effects on oxidative stress, Aβ production and improvement in cognitive function. The finding therefore implicates the potential application of TQ-NLC for management of neurodegenerative diseases particularly AD.